Aggressiveness of Participants in Educational Relations and Psychological Safety of School Environment - Igor V. Badiev (Peoples' Friendship University of Russia (RUDN University), 2021)
The problem of aggression and violence in the educational space is currently quite serious. Illustrative examples of it are numerous publications in the media about acts of aggression exhibited by students against their peers and teachers, about the use of violence by teachers against their students, acute conflicts between the parents of students, sometimes leading to tragic consequences. In this regard, the works devoted to the problem of the psychological safety of the educational environment become very important. The purpose of our research is to identify the factors of psychological safety of the educational environment in the context of the aggressiveness of the participants in educational relations. The study involved 15 292 respondents, including 945 teachers, 6478 parents and 7869 students of grades 7-11 from 34 schools in Ulan-Ude. The following psychodiagnostic techniques were used: Cook - Medley Hostility Scale (CMHS); Questionnaire of Legitimized Aggression by S.N. Enikolopov and N.P. Tsibulsky; Bass - Perry Aggressiveness Questionnaire BPAQ (LA-44) in Russian adaptation by S.N. Enikolopov and N.P. Tsibulsky; questionnaire for students, teachers and parents Psychological diagnostics of the safety of the educational environment at school by I.A. Baeva. The empirical data obtained were subjected to correlation and factor analysis. As a result of the study, the following conclusions were formulated: (1) the psychological safety of students is associated with the peculiarities of the relationships between the teachers and students, between the parents of students and the school, between the parents and other students, between the parents and their children in the context of school education; (2) aggressiveness of students is associated with the level of aggression of their teachers and is not closely related to the level of aggression of their parents; (3) there is an inverse relationship between the aggressiveness of students and their sense of security in relationships with their teachers; (4) aggressiveness of teachers is associated with their satisfaction with the school. There are five areas of relationships that need to be taken into account when designing a safe educational environment: (1) the relationship between parents and students at school; (2) the relationships among teachers and accepted rules of conduct at school; (3) the relationships between teachers and students; (4) family satisfaction with school; (5) teachers satisfaction with the school.